If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + (-7) = -23 + 14x 18x + -7 = -23 + 14x Reorder the terms: -7 + 18x = -23 + 14x Solving -7 + 18x = -23 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -7 + 18x + -14x = -23 + 14x + -14x Combine like terms: 18x + -14x = 4x -7 + 4x = -23 + 14x + -14x Combine like terms: 14x + -14x = 0 -7 + 4x = -23 + 0 -7 + 4x = -23 Add '7' to each side of the equation. -7 + 7 + 4x = -23 + 7 Combine like terms: -7 + 7 = 0 0 + 4x = -23 + 7 4x = -23 + 7 Combine like terms: -23 + 7 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| x+10=-17-2x | | 0=r^2-104.04 | | 6m-10=2m+6 | | 8x+7y=51 | | 8(4x+6)=-8x | | 8+5n=-(-8n-6)-4 | | 25s+40t= | | 9-7x=7x+37 | | 12/a=132/35 | | 3cosx+4=5cosx+5 | | 5cosx=-5sinx | | u/5=5.7 | | -6(x+4)=8(x-4) | | 2/11=4/t-1 | | 4/5x5/9 | | x+x(.1)=150000 | | 1x^2-8+6y^3+3y-12x=2 | | 2+3x=7x-22 | | 3/6h=12/72 | | 8(6n-6)=7-7n | | -4(-2x+5)=9x | | 4/7y-1/3=1/5 | | 785+86= | | (2x+5)=6x+15 | | -2(3x+2)=-14x-2 | | 6x+8=3x+2 | | -388=7(7r+1)-3 | | -14+17=-3(x+8) | | y=34-0.5x | | 2(m-3)+5=19 | | Sen(2x)-2*cosx=0 | | -8n+3=-5n-6 |